Dampak Fenomena Wisata Kuliner Terhadap Kunjungan Wisatawan di Kota Malang, Jawa Timur - Prayogo, Dimas; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA, 2018)
This research discusses about the phenomenon impact of culinary tourism in Malang City, East Java. Which is analyze the characteristic of the tourist such as age, job, and where they from. The impact of culinary tourism phenomenon analyze with the aspect of positive and the negative. The point of view for the impact is in 3 (three) point such as economy, social culture, and the environment. The result of this study is the numbers of tourist departure always raising which is the point of view is still positive. The age of the tourists dominated in 21 – 30 years old. Tourist typology that come to Malang City is incipient mass, the tourist is very considerable about standard of the culinary but they still want the authentic of culinary itself. The impact of culinary tourism is showing the positive result, the tourist and local people feels that culinary tourism make he economy in Malang city being increased and also tourist can learn about the culture.   Keywords : Phenomenon, Impact, Culinary Tourism,  Malang City